Sustainable Concrete with Coconut Fibers to Improve its Mechanical Characteristics in Buildings - Jhonn Anderson, Mas Mendez (2022)
In the search for a dosage that allows us to design a sustainable concrete with greater resistant capacity. Different solutions are proposed that allow us to find the right addition to achieve a better performance in the physical and mechanical characteristics of concrete in fresh and hardened state. For the development of the research, the influence of the addition of coconut fiber in concrete is evaluated. For this reason, various mix designs were developed: The pattern and with the addition of coconut fiber in partial replacement of fine aggregate with designs of 0.50 %, 1.00%, 1.50% and 2.00%, making a total of 90 concrete specimens which are represented in cylindrical and rectangular specimens. For each mixture, tests were carried out for its fresh state and hardened state. From the analysis it is concluded that the most optimal relationship is achieved with 1.00% coconut fiber addition, achieving compressive and flexural strengths at 28 days of 231.60 kg / cm2 and 83.10 kg / cm2, representing percentages of increase in 11.00% and 9.00% respectively.